An emerging role of Prevotella histicola on estrogen deficiency–induced bone loss through the gut microbiota–bone axis in postmenopausal women and in ovariectomized mice. Issue 4 (10th June 2021) - Wang, Zhongxiang; Chen, Kai; Wu, Congcong; Chen, Junhao; Pan, Hao; Liu, Yangbo; Wu, Peng; Yuan, Jiandong; Huang, Furong; Lang, Junzhe; Du, Juanjuan; Xu, Jiake; et al.
ABSTRACT: Background: The gut microbiota (GM)–bone axis has emerged as a crucial mediator of bone homeostasis. Estrogen deficiency–induced bone loss is closely associated with an altered GM. However, the underlying mechanisms remain unclear. Objectives: We sought to explore the putative effects of GM on estrogen deficiency–induced bone loss and determine a potential mechanism. Methods: Fecal samples collected from postmenopausal women with osteoporosis (PMO) and with normal bone mass (PMN) were examined by 16S ribosomal RNA (rRNA) gene sequencing and analysis. Prevotella histicola, a typical species of Prevotella, was orally given to female C57BL6/J mice after ovariectomy [ovariectomized (OVX)]. The primary outcomes were changes in bone microstructures as measured by micro–computed tomography scanning and bone histomorphometry analysis. Secondary outcomes included changes in osteoclast activity, the expression of osteoclastogenic cytokines, and gut permeability, which were measured by ELISA, qRT-PCR, western blot, and immunofluorescence. Results: As demonstrated through 16S rRNA gene sequencing and analysis, the GM in the PMO group featured a significantly decreased proportion of the genus Prevotella in comparison with that in the PMN group (∼60%, P < 0.05). In animal experiments, P. histicola– treated OVX mice maintained a relatively higher bone volume than OVX controls. Mechanistically, the protective effects of P. histicola on bone mass were found to be associated with its modulation of gut permeability as well as its inhibitory effects on osteoclast activity which function by attenuating osteoclastogenic cytokine expression. Conclusions: The GM diversity and composition between the PMN and PMO groups were significantly different. In particular, the proportion of the genus Prevotella was notably higher in the PMN group, demonstrating its potential bone-protective effects on osteoporosis. Further animal study using osteoporotic mice showed P. histicola could prevent estrogen deficiency–induced bone loss through the GM–bone axis. Thus, P. histicola may serve as a therapeutic agent or target for osteoporosis treatment.